Is there a "hidden HIV/AIDS epidemic" in Turkey?: The gap between the numbers and the facts - (:unkn) unknown (My University, 2006)
Since the number of persons living with HIV/AIDS was relatively low compared to the hard-hit countries, HIV/AIDS was not considered as an emerging health problem in Turkey. However Turkey carries a number of factors which enable the spread of HIV/AIDS and the reported rates are accepted to be an underestimation due to the drawbacks of the present surveillance system. This paper discusses the epidemiology of HIV/AIDS in Turkey, factors influencing risk and prevention and the need concerning prevention and control activities in order to address future challenges to combat the epidemic.
Keywords: Control; Epidemiology; HIV/AIDS; Prevention; Turkey